Optimización de la concentración de los azúcares reductores totales de melaza de Saccharum Officinarum L. caña de azúcar en la producción de proteína unicelular de Candida utilis var. Major. Trujillo - Perú. 2018 - Casanova Guajardo, Marlin Deandra (2019)
ABSTRACT The present investigation had as objective decide the optimization of the concentration of the sugar reductors total of molasses of Saccharum officinarum L. ´´cane sugar´´ in the production of single cell protein Candida utilis var. Major. For it a stirred tank reactor of 16 cm. Of heigth with turbine Rushton was built. The preparation of the inoculo was carried out starting from Candida utilis var. Major. C.E.C.T 1430. The médium of culture was formulated starting from molasses dilutions from 15 to 22 g/L of ART (sugar reductors total). The bioprocess was carried out at 25º C to pH 5.0 – 5.5 and during a time of 25 hours. To be found that the biomass and productivy increase progressively (6.93 – 8.37 g/L and 0.277 – 0.3348g/L – h) respectively such as increase the molasses concentration (ART). The yield of Candida utilis var. Major was 56.2% value so closet he teorical yield 56.7%. Finally, the most optimal concentration of ART of molasses of Saccharum officinarum L. ´´cane sugar´´ was 18 g/L.